Application of relative positioning in topographic survey preparations on a full basis in artillery - Projović, Damir M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper deals with the method of GPS relative positioning during topo geodetic survey preparations in artillery. Two Trimble Pro XRS receivers were used as a base station and a rover while a modem was a communication means between the devices. In order to get the results of the survey, statistical methods were applied in the subsequent data analysis. The results show a significantly reduced likelihood of errors at work in comparison to required values. The application of relative positioning during topographic survey preparations on a full basis provides much faster operation and higher accuracy than the prescribed one.